An enlarged congenital dermoid cyst under the floor of mouth; a rare entity - Muhammad Hamza Rana; Muhammad Saleem (Journal of University Medical & Dental College, 2022)
Dermoid cysts are rare congenital anomalies that arise due to the retention of germinal epithelium. A 26-year-old man was admitted for having complaints of a large, painless, soft sublingual mass with dysphagia and snoring. After general and systemic examination, the patient underwent surgical resection via a cervical approach revealing a (10*7 cm) cyst. Treatment of these sublingual cysts is surgical resection depending upon the size of the tumor.